TINGKAT KOMPETENSI PROFESIONAL PENYULUH PERTANIAN DI KABUPATEN KAMPAR - Rosnita '; Roza Yulida; Eri Sayamar; Kausar '; Cepriadi ' (Indonesian Journal of Agricultural Economics, 2014)
This research aims to study the implementation of agricultural extension, analyze the level of professional competence and study the problems of agricultural extension education in improving the competency of agricultural extension in the Kampar Regency. Implementation of education in the Kampar Regency has been running with good views of the elements that influence the extension of agricultural extension, targeted outreach, media outreach, extension materials, time extension, the extension, facilities and infrastructure. The level of professional competence in the district agricultural extension Kampar obtained a score of 4.16 with a competent category. It can be seen from the sub-variables: the competent administrative competence with a score of 4,08, a very competent program planning very competence with a score of 4.47, the competence of the program with a score of 4.27 very competent, very competent teaching competence with a score 4.24, competency competent communication with a score of 4.12, competence competent understanding of human behavior with a score of 3.88, maintaining professionalism competent with scores of 3.61; very competent and competency evaluation with a score of 4.60. Problems counseling in improving the competence of extension are: labor limited extension, which extension should receive extension target area build the village and lack of media consumption extension of information that is required to develop professionalism.